Pemetaan instrumen psikologis dalam penelitian thalassemia: Tinjauan literatur - Agung, Mirza Aaliyah (Maliki Interdisciplinary Journal, 2026)
Thalassemia is a genetic blood disorder that has long-term impacts on the physical and psychological condition of sufferers. Individuals with thalassemia major face challenges such as regular transfusions, medical complications, and activity limitations that can potentially reduce quality of life, increase anxiety, depression, and psychological distress. This article aims to review the literature related to the psychological impact of thalassemia and psychological measurement tools commonly used to assess mental aspects of patients. The method used is a systematic literature review through open access journal searches from Google Scholar, PubMed, and DOAJ. The review results indicate that frequently used measurement tools include the WHOQOL-BREF, Pediatric Quality of Life Inventory (PedsQL), Hospital Anxiety and Depression Scale (HADS), Strength and Difficulties Questionnaire (SDQ), and Brief COPE. This review emphasizes the importance of structured psychological support to improve patients’ quality of life. The article’s findings are expected to provide a basis for further research and appropriate assessment-based psychosocial interventions.